A deep insight into ferroptosis in lung disease: facts and perspectives - Zhang, Fan; Xiang, Yu; Ma, Qiao; Guo, E.; Zeng, Xiansheng (Frontiers in Oncology, 2024)
In the last decade, ferroptosis has received much attention from the scientific research community. It differs from other modes of cell death at the morphological, biochemical, and genetic levels. Ferroptosis is mainly characterized by non-apoptotic iron-dependent cell death caused by iron-dependent lipid peroxide excess and is accompanied by abnormal iron metabolism and oxidative stress. In recent years, more and more studies have shown that ferroptosis is closely related to the occurrence and development of lung diseases. COPD, asthma, lung injury, lung fibrosis, lung cancer, lung infection and other respiratory diseases have become the third most common chronic diseases worldwide, bringing serious economic and psychological burden to people around the world. However, the exact mechanism by which ferroptosis is involved in the development and progression of lung diseases has not been fully revealed. In this manuscript, we describe the mechanism of ferroptosis, targeting of ferroptosis related signaling pathways and proteins, summarize the relationship between ferroptosis and respiratory diseases, and explore the intervention and targeted therapy of ferroptosis for respiratory diseases.